دور الطاقة المتجددة في تحقيق الأمن الطاقوي في سورية في مرحلة إعادة إعمار سورية - الكفري مصطفى; عيسى جيداء (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Most global studies confirm that Traditional energy sources will be depleted in a few decades So the world started research and studies on alternative sources of conventional energy. we knew Nuclear energy and its negative resulting and destructive effects of mankind. Then the research adopted green renewable energy sources Which provides energy without fear of depletion and at the same time non-destructive environment and climate Such as solar, wind, water and biomass as well as geothermal and hydrogen. Syria like any other country will suffer from the depletion of traditional energy sources Regardless of what these sources suffered from destruction and depletion during the period of war on Syria. However, this depletion requires accelerating the pace of developed countries towards renewable energy sources Which Syria has a large quantity of them. Here comes the search to answer the following questions Are Renewable Energy Sources Achieving Energy Security in Syria? Can we rely on investment in Renewable Energy Sources in reconstruction phase of Syria? The research concluded that investing in renewable energy achieves energy security in Syria and that reliance on our available national sources of renewable energy is one of the most important requirements for reconstruction. تؤكد أغلب الدراسات العالمية بأن مصادر الطاقة التقليدية ستنضب خلال عقود قليلة. لذا بدأ العالم بإجراء البحوث والدراسات عن مصادر بديلة للطاقة التقليدية، فكانت الطاقة النووية وما نتج عنها من آثار سلبية ومدمرة للبشرية، ثم وصلت الأبحاث إلى تبني مصادر الطاقة المتجددة الخضراء التي تؤمن الطاقة دون خشية النضوب، وبنفس الوقت غير مدمرة للبيئة والمناخ، كطاقة الشمس والرياح والماء والكتلة الحيوية بالإضافة إلى طاقة حرارة باطن الأرض والهيدروجين. وسورية ستعاني كأي دولة من نضوب مصادر الطاقة التقليدية، بغض النظر عما تعرضت له هذه المصادر من تدمير واستنزاف خلال فترة الحرب على سورية، ولكن هذا الاستنزاف يستوجب التسريع في السير على خطى الدول المتقدمة نحو مصادر الطاقة المتجددة؛ والتي تمتلك سورية كموناً واسعاً منها، وهنا يأتي البحث للإجابة على التساؤلات التالية: هل تحقق مصادر الطاقة المتجددة أمن الطاقة في سورية؟، وهل نستطيع الاعتماد على الاستثمار فيها في مرحلة إعادة إعمار سورية؟، وخلص البحث أن الاستثمار في الطاقة المتجددة يحقق الأمن الطاقوي في سورية، وأن الاعتماد على مصادرنا الوطنية المتاحة من الطاقة المتجددة يعد من أهم متطلبات إعادة الإعمار.